El gobierno de la carretera - Ilizarbe, Carmen (2025)
Clashes over extractive projects in Peru between the State and peasant communities have increased and expanded throughout the country during the 21st century, despite policies promoting dialogue and negotiation encouraged by various governments. Rather, the use of exceptional regimes, in the form of declaration of state of emergency to address protests, has become normalized, and in some cases, this normalization has allowed for the establishment of authoritarian enclaves. Why are authoritarian enclaves established? How are they governed? What mechanisms make authoritarian government possible? This article studies, analyzing the history of the approval and construction of a mining corridor, how and why the Peruvian State instituted an authoritarian enclave in the surroundings of the Las Bambas mining project, between 2015 and 2020. The analysis is based on three analytical inputs: 1) the reconstruction of the legal-juridical process that institutionalizes the authoritarian enclave, 2) a characterization of the type of government and governmental mechanisms used in this geopolitical space, and 3) an ethnographic account of the dynamics of circulation and immobility that are imposed in the corridor, and reveal the functioning of the authoritarian enclave.